2007
DOI: 10.1175/jas3926.1
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Katabatic Flow and Mountain Waves. Part II: Case Study Analysis and Conceptual Model

Abstract: Via numerical analysis of detailed simulations of an early September 1993 case night, the authors develop a conceptual model of the interaction of katabatic flow in the nocturnal boundary layer with mountain waves (MKI). A companion paper (Part I) describes the synoptic and mesoscale observations of the case night from the Atmospheric Studies in Complex Terrain (ASCOT) experiment and idealized numerical simulations that manifest components of the conceptual model of MKI presented herein. The reader is also ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Poulos et al (2007), except for velocity and not KE when investigating the flow in the eldorado Canyon in Colorado. They thus had to consider more terms: advection, pressure gradient, gravity, coriolis effects, and turbulent momentum flux contributing to local changes in wind velocity.…”
Section: The Methodologymentioning
confidence: 99%
“…Poulos et al (2007), except for velocity and not KE when investigating the flow in the eldorado Canyon in Colorado. They thus had to consider more terms: advection, pressure gradient, gravity, coriolis effects, and turbulent momentum flux contributing to local changes in wind velocity.…”
Section: The Methodologymentioning
confidence: 99%
“…Durran [1990]) suggest that downslope wind storms can be forced by mountain waves or a combination of katabatic flows and mountain waves [Poulos et al, 2000[Poulos et al, , 2007. Gravity waves were also observed during a katabatic wind event in West Greenland [Heinemann, 1999] and Doyle et al [2005] observed large-amplitude wave breaking during an individual DWE in Ammassalik.…”
Section: Modis Visible Images During Individual Events and Analyze Ammentioning
confidence: 96%
“…Interactions between gravitationally driven flows and mountain waves have been studied by Poulos et al [2000Poulos et al [ , 2007 for different Froude number regimes. Using an upstream wind speed of 30 m s −1 for the strong wind event, a stability of = 0.02 s −1 and a mountain height of 3000 m, the Froude number is close to 0.5 for the strong wind event.…”
Section: Mountain Wave -Gravity Current Interactionmentioning
confidence: 99%
See 2 more Smart Citations